2018
DOI: 10.5752/p.2358-3428.2018v22n45p151-162
|View full text |Cite
|
Sign up to set email alerts
|

O crime ambiental de Mariana: omissão e conivência da mídia brasileira

Abstract: O objetivo deste artigo, -- produzido pelo grupo de Ensino, Pesquisa e Extensão “Estação Liberdade”, da UFMG--, foi realizar uma análise do que foi publicado (e como foi publicado) sobre o crime ambiental e humano em Mariana (MG)--, em veículos da mídia tradicional regional e nacional. Este estudo foi feito através da análise do discurso e do cruzamento de dados relativos à história do setor minerário em Minas Gerais. Como resultado, verificou-se a existência de uma cobertura falha e que primou por silenciar o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indeed, conclusions from a study that evaluated the mediatic speech about Fundão dam outburst shown that media reports had a sensationalist and fatalistic focus in environmental issues without clarifying the problem in greater depth or presenting an educational approach. Besides, different predominant discourses about the disaster were identified, sometimes guided by specific interests (Carrato et al, 2018;Fontes & Lopes, 2017). Therefore, the posture of media at natural disasters by disseminating of incorrect, insufficient, opportunistic and outdated information has been contributing to increase the skepticism and loss of confidence in disclosed information about quality of water and food.…”
Section: Residents' Perception About Disclosed Informationmentioning
confidence: 99%
“…Indeed, conclusions from a study that evaluated the mediatic speech about Fundão dam outburst shown that media reports had a sensationalist and fatalistic focus in environmental issues without clarifying the problem in greater depth or presenting an educational approach. Besides, different predominant discourses about the disaster were identified, sometimes guided by specific interests (Carrato et al, 2018;Fontes & Lopes, 2017). Therefore, the posture of media at natural disasters by disseminating of incorrect, insufficient, opportunistic and outdated information has been contributing to increase the skepticism and loss of confidence in disclosed information about quality of water and food.…”
Section: Residents' Perception About Disclosed Informationmentioning
confidence: 99%